UPAYA MENINGKATKAN BERPIKIR KRITIS MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING PADA MATA PELAJARAN SEJARAH KELAS 10-E9 SMA NEGERI 1 TAMAN - Agung Agung; Liana Liana; Derry Anggraeni Purwatiningsih (Universitas Muhammadiyah Gresik, 2023)
This classroom action research was conducted because of low critical thinking skills in the history subject of students in grade 10-E9 SMA Negeri 1 Taman. The purpose of this research is to improve critical thinking skills through the Discovery Learning learning model. The results of the study in cycle I showed an average value of 68 and cycle II increased to an average value of 82. The results of the regression test were Y = 60.987 + 0.238 and an increase of 17.1% which can be seen in the Summary table using SPSS 25. That is, the achievement of students' critical thinking skills through the Discovery Learning model in history subjects class 10-E9 SMA Negeri 1 Taman has increased. Based on this description it can be concluded that there is an increase in students' critical thinking skills in history subjects class 10-E9 SMA Negeri 1 Taman.